Operative and conservative treatment of right colon diverticulitis (Annals of Medical Research, 2021)
Aim: This study assessed the results of conservative and surgical treatment of right colon diverticulitis. Right colon diverticula contain all layers of the colon and are called true diverticula. Perforation of these diverticula is observed less frequently due to their full thickness.Materials and Methods: 150 patients treated for colonic diverticulitis between 2015-2020 were retrospectively screened. Following exclusions, a total of 26 patients data were assessed. The patients were divided into two groups as conservative or surgical treatment. The outcomes for these two groups were compared and analyzed.Results: Most patients in the sample were female (n=18, 69%). The average age was 47 (22-83). Data from the conservative treatment group (n=17, 65%) and the surgical treatment group (n=9, 35%) were examined. Comorbidity, recurrence, and white blood cell count were all greater following conservative treatment (p> 0.05). In the surgical group, two (22% of the group) patients developed wound infections. Patients with fever at admission were in the surgical group (p 0.01). All patients in the conservative group had a Hinchey classification of 1a, while those in the surgical group were Hinchey 1a, 1b, and 3 (p 0.05). The median hospital stay was higher for the surgical group (p 0.05). No mortality was observed.Conclusion: Right colon diverticulitis has low complications and it can be treated conservatively. The differential diagnosis of rightsided colonic diverticulitis should be kept in mind when relevant symptoms present to prevent unnecessary surgeries. Surgical treatment is inevitable in instances of recurrent diverticulitis, generalized peritonitis, and suspected malignancy.
Keywords: Diverticulum; diverticula; surgery; appendicitis sigmoid volvulus; caecum